Demand Stimulus as Social Policy - Alan Auerbach; Yuriy Gorodnichenko; Daniel Murphy (Institute of Labor Economics (IZA), 2022)
We exploit a panel of city-level data with rich demographic information to estimate the distributional effects of Department of Defense spending and its effects on a range of social outcomes. The income generated by defense spending accrues predominantly to households without a bachelor's degree. These households as well as Black households tend to disproportionately benefit from this spending. Defense spending also promotes a range of beneficial social outcomes that are often targeted by government programs, including reductions in poverty, divorce rates, disability rates, and mortality rates, as well as increases in homeownership, health insurance rates, and occupational prestige. We compare the effects of defense spending with the effects of general demand shocks and explore reasons for the differential effects of the shocks.
Keywords: E6; H3; 330; fiscal policy; inequality; social policy